A voz (popular) que informa : ecos de um discurso político nas páginas do Jornal dos Bairros (1976-1981) - Daniela Lacerda de Almeida (2010)
In 1974, with the take office of the new military president, General Ernesto Geisel, the Brazilian government began a process of political opening that aimed to ensure an easing of social and political tensions, created after the civil-military coup of 1964. In pursuit of this political openness, Geisel's successor, Gen. Joao Batista Figueiredo followed the same assumptions for continuing liberalization measures and to increase levels of political participation, according to planning and state control. This whole process, despite having been marked by advances and setbacks for the government, contributed to the emergence and strengthening of social movements, especially the labor movement and associations of slum dwellers.It is in this context that created the Jornal dos Bairros (Journal of Neighborhoods), bi-weekly publication that circulated in the industrial region of Belo Horizonte, Contagem, Ibirité and Betim, from September 1976 to December 1981. The initial goal was to portray the problems and issues important to the residents of the region covered by the newspaper, but changes in the situation of the country contributed to changes in the profile of the journal. This thesis attempts to analyze the articles published by this journal to uncover aspects of daily life experienced by residents of neighborhoods and also establish a relationship between the transformations undergone by the newspaper and the political context and social experience for that country.